Processes of appropriation of space and neighborhood sociability in a large urban complex located in the city of Buenos Aires - Girola, María Florencia (2007)
This article aspires to be a contribution to an anthropological approach on housing and habitat, understanding both notions as complex socio-cultural phenomena. In this sense, our aim is to reflect —from an ethnographic point of view— on the processes whereby living spaces are appropriated, as well as to reflect on certain features that neighbors’ sociability adopts in a social-interest housing complex built as a large urban unit in the South-East area of Buenos Aires, specifically in the barrio of Villa Soldati. In order to do so, we made a distinction between planned spaces and developed spaces, and also differentiated three uses of the common and shared spaces in this particular housing complex: spaces with idle use, incompatible use and uncivil use. The qualitative methodology used in this study was based on a still ongoing field work, which included field observation and non-directive in-depth interviews, as well as the analysis of written secondary sources —official documents, statistic data, journalistic articles—.